A Depression Containing CO2-Enriched Water at the Bottom of Lake Monoun, Cameroon, and Implications for the 1984 Limnic Eruption - Ohba, Takeshi; Oginuma, Yu; Saiki, Kazuto; Kusakabe, Minoru; Issa; Fouepe, Takounjou A.; Ntchantcho, Romaric; Tanyileke, Gregory; Hell, Joseph V. (Frontiers in Earth Science, 2022)
In 1984, a limnic eruption occurred in Lake Monoun, Cameroon, and the CO2 gas released from the lake surface resulted in casualties in the neighboring communities. Subsequent scientific research revealed that the CO2 gas released from the lake surface was CO2 of magmatic origin dissolved in the lake water; however, the mechanism of that limnic eruption remains unclear. In this study, we analyzed in detail the lake-bottom bathymetry of the eastern basin, i.e., one of the three basins in Lake Monoun, to understand the mechanism of the 1984 limnic eruption. We discovered two significant depressions at the lake bottom near the scarp and obtained vertical profiles of several parameters of the lake water at the depression locations. The northeastern depression (D1) was ∼ 1.2 m deeper than the lake bottom and contained water with higher temperature and electrical conductivity and lower pH relative to the lake water. Conversely, the southern depression (D2) was ∼ 2.2 m deeper than the lake bottom, and there were no anomalies regarding its water parameters. Although the warm water discharged from the bottom of D1 was not saturated with dissolved CO2, bubbles likely existed at the bottom of D1, influenced by the partial pressure of dissolved CH4 in the lake water. Our results suggest that just before the 1984 limnic eruption, water containing high concentrations of dissolved CO2 was discharged from D1; this water would have reached the lake surface with bubbles. According to earlier numerical simulations of the limnic eruption, rising bubbles could have induced the limnic eruption. The rising bubbles entrained the surrounding lake water containing high concentrations of dissolved CO2, which amplified the flow rate of CO2 degassing from the lake water and resulted in a limnic eruption. The limnic eruption that occurred just above D1 displaced lake water on the eastern shore. It is estimated that the impact of the displaced water eroded the scarp and deposited sediment as a mound near D1. A similar mound also exists near D2, suggesting that D2 is a trace of another limnic eruption that occurred earlier than 1984. Of the three basins that make up Lake Monoun, the two smaller basins to the west have high concentrations of dissolved CO2 in their deep waters. This dissolved CO2 was not supplied from the bottom of the basins but is likely a remnant of the dissolved CO2 that existed in 2003 before the start of artificial CO2 degassing. Our results suggest that another limnic eruption occurred before 1984. Lake Monoun may have experienced several limnic eruptions in the past. If the artificial degassing of CO2 is not continued, the water released from D1, containing high concentrations of dissolved CO2, will increase the concentration of dissolved CO2 in the lake water, and the bubbles rising from D1 will cause another limnic eruption. In the future, the flux of CO2 supplied from D1 may increase and exceed the flux of CO2 removed by the artificial degassing, potentially increasing the amount of CO2 accumulated in the lake water. The regular monitoring of the CO2 amount in lake water should be also continued.